Exploring the relationship between level of cognitive ability in mathematics within two different schools in Tapah / Aina Nafisya Shuhaimi ... [et al.] - Aina Nafisya, Shuhaimi; Muhammad Hazim, Ismail; Norfarahanim, Sahar; Nur Hanim, Abdul Jabar; Nurul Farihah, Yaakob; Nor Faezah, Mohamad Razi (UiTM Press, 2020)
Cognitive ability in Mathematics has been widely discussed in various platforms. A total of 248 students from two schools in Tapah was selected in this study. The result showed that the cognitive level for of the students of SMK Sri Tapah and SMK Buyong Adil was found to be at moderate level where the score for each of the cognitive level lies between 20% to 50 %. Furthermore, this study identified the existence of a moderate relationship between all cognitive levels by using Correlation Analysis. Meanwhile, Mann Whitney test was used to test the differences of students performance from both schools and it showed that the students from SMK Buyong Adil were statistically greater for Knowing level (C1) SMK Buyong Adil (Mdn=0.5 marks), Understanding level (C2) (Mdn=0.5 marks), Applying level (C3) (Mdn=0.5 marks), Creating level (C6) (Mdn=1 marks) than students from SMK Sri Tapah. However, students from SMK Sri Tapah were found to be greater in Evaluating level (C5) (Mdn=1 marks) than students from SMK Buyong Adil. Overall this study found that the level of cognitive ability in both schools in Tapah is still at a moderate level and have to be improved.